A Dynamic Community of Discovery: Planning, Learning, and Change - Gordon, Michelle; Ireland, Martha; Wong, Mina (International Review of Research in Open and Distributed Learning, 2011)
Ryerson University’s Prior Learning and Competency Evaluation and Documentation (PLACED) program is funded by the Government of Ontario to engage internationally educated professionals (IEPs), employers, and regulatory/occupational bodies in the use of competency-based practices. In 2008, the authors created a self-assessment tool for IEPs that would build a portfolio reflecting an individual’s knowledge and skills while introducing him or her to aspects of the Canadian workplace and labour market. The authors felt that this tool would be useful to assist IEPs in considering their career options and wanted to create an online workshop that would provide flexibility to users whose priorities were most likely work and family obligations. This short project description will capture a) why the self-assessment tool was developed; (b) how we fostered participants’ self-efficacy; c) how we used Blackboard; (d) what the participants gained from the workshop; and (e) how the workshop has evolved based on facilitators’ observations, participants’ feedback, and an external organization’s request for customizing the workshop. In working together to design the online workshop, IEPs’ Self-Assessment and Planning, we focused on two main concepts: self-assessment and career planning. With that in mind, we set out in the workshop to bolster self-discovery, self-efficacy, individualized research skills, action planning, and ongoing professional development. The learning platform was Blackboard, which is used across Ryerson University in both classroom and online learning.